Temporal Variation in the Fatty Acid Composition of Ovigerous Females and Embryos of the Squat Lobster Pleuroncodes Monodon (Decapoda, Munididae) - Guzman-Rivas, F (Cambridge University Press, 2018)
Pleuroncodes monodon, an important fishery resource and key species in the Humboldt Current Large Marine ecosystem, has a prolonged reproductive period from winter until end of summer, and during this time females incubating their embryos are exposed to seasonal variation in food availability and in temperature. Additionally, in order to ensure successful reproduction and survival of embryos, changes occur in the main internal reserves and/or sources of energy of P. monodon. The aim of this study was to determine the extent of seasonal variation (winter vs summer) in the lipid content and fatty acid composition of ovigerous females and their embryos. The results show that a higher percentage of saturated and polyunsaturated fatty acids are found in females in winter. Similarly, the composition of fatty acids in embryos found here indicates that winter embryos have more saturated fatty acids and essential fatty acids (C18:2n6cis, C18:3n6 and C22:6n3) than do summer embryos. According to PCA analysis of fatty acid profile, samples from summer may be distinguished into two isolated groups with conspicuous variations in fatty acids profile of embryo and hepatopancreas. While in winter, the opposite pattern occurs in the fatty acid profile of embryo and hepatopancreas. These variations may be related to relevant physiological processes (reproduction and growth) and of their ontogeny (development and survival of offspring). Seasonal variation in the lipid content and composition of fatty acids of P. monodon could directly impact this species reproduction and survival and subsequently could have consequences on the food web and fishery exploitation. © Marine Biological Association of the United Kingdom 2017.